Obraz inteligencji w parodyjnym świetle na podstawie powieści „Krokodyl” Włodzimierza Kantora - Tracz, Agnieszka (Studia Rossica Posnaniensia, 2015)
This article describes a parody of the Russian intelligentsia in the 1970s. It also discusses the motif of a crocodile in Russian culture, i.e. Pomadov and Oblomov, and a longing for freedom. It also aims to show the atrocities of everyday life.